"Black Board" split or merger: the paradoxes of historical destiny - Парахіна М. (Видавничо-поліграфічний центр "Київський університет", 2013)
Death B.Khmelnitsky June 27, 1657 changed the timetable of political parties in the relationship Hetmanate and Moscow, and prompted the letter to review the agreements on the status of Ukraine as a vassal of Moscow, and Nijinsky events of 1663, known today under the name Black Council considered the Rubicon that finally divided the Ukrainian state in two. Much of this was driven by its perception of the Cossack chronicles and the spread of the XIX century. Ukrainian society (especially among intellectuals) of the same work Panteleimon Kulish. Nizhynska Council was key to ruins, since it is largely prysluzhylas to split the state into two Ukrainian Hetman – Left-and right-bank. It should be noted that Moscow back in 1662 sought to Ukraine is divided into two parts along the Dnieper. The Russian side was aware that the appearance of the Left government authorized share Ukraine not only de facto but also de jure and significantly reduce the chances of Moscow to get under his domination of all Ukrainian lands.

Смерть Б.Хмельницького 27 червня 1657 р. змінила розклад політичних сил у відносинах між Гетьманщиною і Москвою, та підштовхнула останню до перегляду домовленостей по статусу України як васала Москви, а ніжинські події 1663 р., відомі на сьогодні під назвою Чорна Рада, вважаються тим рубіконом, що остаточно розділили Українську державу на дві частини. Багато в чому це було спричинено її сприйняттям козацькими літописами, а також поширенню в XIX ст. в українському суспільстві (передусім серед інтелігенції) однойменного твору Пантелеймона Куліша. Ніжинська рада стала ключовим моментом Руїни, оскільки саме вона багато в чому прислужилась до розколу Української держави на два гетьманства – Ліво- і Правобережне. Слід зазначити, що Москва ще у 1662 р. хотіла бачити Україну поділеною на дві частини по Дніпру. Російська сторона усвідомлювала, що поява на Лівобережжі повноважного уряду розділить Україну не лише де-факто, але й де-юре і суттєво зменшить шанси Москви отримати під свою зверхність всі українські землі.
«Чорна рада» розкол чи об'єднання: парадокси історичної долі
Keywords: Ukraine; Nizhin; Black Board; state; Hetman; України; Ніжин; Чорна рада; державність; Гетьманщина